THIRD HAND : A solution for the fuel tank assembly at Scania Södertälje - Westerberg, SandraMarie; Ödesjö, Tova (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2023)
Scania recently introduced a new fuel tank design. This new design arose a need for extra help when mounting the tank in production, which was solved with two little hooks on each tank. These hooks are today known as the current third hand solution. Not only have these hooks added additional costs, but they have also significantly compromised the work environment at the fuel tank assembly. Since an assembler can assemble up to 40 tanks in a day, even a small change would make a big difference. The aim of this thesis was therefore to improve the work environment for the fuel tank assemblers in the production at Scania Södertälje. The aim was also to discover an alternative solution that was both financially feasible and environmentally sustainable when compared to the existing hook solution. Therefore the objective was to create a new concept for holding the fuel tank in place during assembly, taking into account cost reduction and improved safety in production. The thesis was performed at Luleå University of Technology and Scania Södertälje during spring 2023 within the topic of Industrial design engineering. The development of the concept has been done with the user in focus, a so called human-centred/user-centred work. To reach a concept that is designed for the user, the user has been involved throughout the entire project. Additionally a lot of focus has also been on topics that will help improve the concept from a human-centred view, for example ergonomics and usability. The project followed a linear process, with iterations when needed. The phases of the project were planning, context, ideation and implementation. During the project a bunch of creative methods have been utilized to reach the best result possible. The methods are in many cases chosen because they will contribute to a human-centred design. Example of used methods are interviews, user journey, speedstorming and prototypes. The thesis resulted in a concept for mounting the fuel tanks in production. The concept is a redesign of the existing ...